ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN INVESTOR UNTUK BERTRANSAKSI DI BEI (Studi Pada Masyarakat Bengkulu) - Herry Novrianda; Aan Shar; Dhimas Setyo Nugroho (The Manager Review, 2020)
The purpose of this research is to identify the most influential factors including cultural factors, social factors, personal factors and psychological factors on the investor's decision to trade on the IDX. This research is descriptive research, with the study population is Bengkulu community investors who transact on the IDX with the sampling technique used accidental sampling. The data analysis technique used is the validity and reliability test and multiple linear regression analysis. The results of this study are cultural, social, personal and psychological factors partially or simultaneously a positive and significant effect on investors' decisions to trade on the IDX. Psychological factors are the most dominant factors influencing investors' decisions to trade on the IDX.